Dynamic response of flexible retaining walls. - Younan, A. H. (Earthquake engineering & structural dynamics.)
Making use of an extension of a recently proposed, relatively simple, approximate method of analysis, a critical evaluation is made of the response to horizontal ground shaking of flexible walls retaining a uniform, linear, viscoelastic stratum of constant thickness and semi-infinite extent in the horizontal direction. Both cantilever, and top supported walls are examined. Following a detailed description of the method and of its rate of convergence, comprehensive numerical solutions are presented that elucidate the action of the system and the effects of the various parameters involved. The parameters varied inlucd the flexibility of the wall, the condition of top support, and the characteristics of the ground motion. The effects of both harmonic base motions and an actual earthquake record are examined. Special attention is paid to the effects of long period, effectively static excitations. A maximum dynamic response is then expressed as the product of the corresponding static response and an appropriate amplification or deamplification factor. The response quantities examined include the displacements of the wall relative to its moving base, the dynamic wall pressures and the total wall force, base shear and base moment.